The who and what of inclusive education—Profiles of student teachers' attitudes toward inclusive education - Selisko, Tom Jannick; Eckert, Christine; Perels, Franziska (Frontiers in Education, 2024)
The present study investigated the relationship between different attitudes toward inclusive education. It draws from the Framework of Inclusive Education by assuming a reciprocal relationship between learning theory beliefs, models of disability, and the assessment of joined education, resulting in consistent attitudes toward inclusion. The study investigated attitudes toward inclusion by applying a person-centered approach (latent profile analysis; LPA) to a sample of N = 138 student teachers. The results suggest a two-class solution: firstly, a consistent exclusive profile combining higher transmissive beliefs of learning and teaching and a preference for exclusion; secondly, a general inclusive profile that combines support for functional and full inclusion, relational and social models of disability, and a cognitive, constructivist learning theory. The profile distribution appeared to be related to teacher self-efficacy, but not to gender or the educational stage of prospective teaching practice.